The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1017/s1481803500012732
|View full text |Cite
|
Sign up to set email alerts
|

Low-impact pelvic fractures in the emergency department

Abstract: Objective: We examined the records of patients presenting to the emergency department (ED) with low-impact pelvic fractures. We describe frequency, demographics, management and patient outcomes in terms of ambulatory ability, living independence and mortality. Methods: Patients treated for a pelvic fracture over a 2-year period in Kingston, Ont., were identified. We performed a retrospective hospital record review to distinguish high- versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
1
18
0
3
Order By: Relevance
“…One potential limitation of the study is that we did not compare the comorbid conditions of the study sample to the entire NTDB. However, in a Canadian study, the authors found that more than 90% of octogenarians admitted to the emergency room with pelvis fractures had medical comorbidities [20]. Therefore, we can assume that our octogenarian patients also have similar comorbidities.…”
Section: Discussionmentioning
confidence: 89%
“…One potential limitation of the study is that we did not compare the comorbid conditions of the study sample to the entire NTDB. However, in a Canadian study, the authors found that more than 90% of octogenarians admitted to the emergency room with pelvis fractures had medical comorbidities [20]. Therefore, we can assume that our octogenarian patients also have similar comorbidities.…”
Section: Discussionmentioning
confidence: 89%
“…Clinical pathways characterized by multidisciplinarity have been recently re-worked to cope with problems specific to these patients and to secure their best possible outcome [ 5 ]. A constantly-rising number of fragility pelvic fractures has also been reported [ 6 ]. Their clinical picture, radiological morphology and intrinsic instability range widely from nearly stable to completely unstable conditions.…”
Section: Introductionmentioning
confidence: 99%
“…También muy es frecuente la afectación acetabular. Dodge y Brison [17] estudiaron 77 fracturas de baja energía con una edad media de 81 años encontrando un 22% de fracturas de cotilo. En nuestra revisión se observó que en el 36.7% de las fracturas el trazo comprometía el cotilo.…”
Section: Discussionunclassified
“…Otros estudios de características similares observan datos muy variables. Morris et al [2] registraron una mortalidad al año del 27%, Dodge & Brison [17] del 17% y Koval et al [9] del 9,5%. Estos son datos muy similares a la mortalidad anual observada en las fracturas de cadera, cuyas cifras son del 14 al 36% [26] .…”
Section: Discussionunclassified